Digital (dis)connectivity in fraught contexts: The case of gay refugees in Belgium. (October 2020) - Dhoest, Alexander
The key role of digital and mobile media for refugees is increasingly acknowledged, but while the literature on the topic tends to celebrate the advantages of digital media, it is important to also acknowledge limitations. Thus, the focus on the creation and maintenance of connections through digital media may obscure experiences and practices of disconnection. This is certainly the case for forced migrants with non-normative sexual orientations, for whom experiences of homophobia within the family and ethno-cultural community in the country of origin may extend to fraught situations in the country of residence. As with digital media in general, it is important to consider the 'offline' social and cultural conditions determining online media uses. This article focuses on the specific challenges for lesbian, gay, bisexual, transgender and queer refugees, both in general and in Belgium, drawing on desk research and expert interviews, as well as nine in-depth interviews with gay-identifying male refugees. While the refugees are relatively positive about the Belgian situation, they do identify a number of challenges. They use digital media to stay connected to family and other people in the country of origin, but often this connection has become difficult. Social media and dating sites also offer a way to connect to other gay men, but these connections can be equally fraught, particularly in the country of origin for danger of exposure but also in Belgium as social media transcend national boundaries. For this reason, some participants created new or parallel profiles, to keep their gay lives disconnected from their family lives. Overall, then, digital media are a tool not only of connection but also of strategic disconnection for gay refugees.